2017
DOI: 10.1016/j.ijppaw.2017.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Babesia peircei and Babesia ugwidiensis provides insight into the evolution and host specificity of avian piroplasmids

Abstract: There are 16 recognized species of avian-infecting Babesia spp. (Piroplasmida: Babesiidae). While the classification of piroplasmids has been historically based on morphological differences, geographic isolation and presumed host and/or vector specificities, recent studies employing gene sequence analysis have provided insight into their phylogenetic relationships and host distribution and specificity. In this study, we analyzed the sequences of the 18S rRNA gene and ITS-1 and ITS-2 regions of two Babesia spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…More than 100 species of Babesia have been described. The majority have been recorded in mammals, and 16 species have so far been described from avian hosts [6,7]. In Europe, the roe deer (Capreolus capreolus) is considered the main vertebrate host of both Babesia capreoli and Babesia venatorum [8,9], while Babesia divergens is prevalent in cattle in southern Sweden [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…More than 100 species of Babesia have been described. The majority have been recorded in mammals, and 16 species have so far been described from avian hosts [6,7]. In Europe, the roe deer (Capreolus capreolus) is considered the main vertebrate host of both Babesia capreoli and Babesia venatorum [8,9], while Babesia divergens is prevalent in cattle in southern Sweden [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…group can be distinguished into at least two genera (Clade I and Clade II as defined by Schnittger et al [ 2 ], Lack et al [ 20 ], Schreeg et al [ 22 ]). Meanwhile, it is worth noting that additional piroplasmid genera have been identified that are not considered in the present study as no genome sequences are available from species pertaining to these groups [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite their inherent limitations in terms of specificity, the primers targeting the 18S rRNA gene employed in this study have been successfully employed in other studies to detect Babesia spp. in birds (Yabsley et al 2006;Yabsley et al 2009), including penguins (Vanstreels et al 2015;Yabsley et al 2017). Unfortunately, the 18S rRNA gene sequence produced by Montero et al (2016) for Babesia sp.…”
Section: Discussionmentioning
confidence: 99%